2015
DOI: 10.4097/kjae.2015.68.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oxycodone and fentanyl for postoperative patient-controlled analgesia after laparoscopic gynecological surgery

Abstract: BackgroundOpioids are widely used in boluses and patient-controlled analgesia (PCA) for postoperative pain control. In this study, we compared the effects of oxycodone and fentanyl on postoperative pain in patients with intravenous patient-controlled analgesia (IV-PCA) after laparoscopic gynecological surgery.MethodsSeventy-four patients undergoing elective total laparoscopic hysterectomy or laparoscopic myomectomy were randomly assigned to the administration of either fentanyl or oxycodone using IV-PCA (poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 21 publications
4
78
0
Order By: Relevance
“…[20] In another recent similar study, the potency ratio was 60:1, and both agents were found to provide similar analgesic efficacy and similar rates of adverse events. [21] Overall, the potency ratio of fentanyl to morphine has a range of 60–100:1. After conducting a series of pilot study, we originally performed this study under the hypothesis that the potency ratio of oxycodone to fentanyl was 60:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] In another recent similar study, the potency ratio was 60:1, and both agents were found to provide similar analgesic efficacy and similar rates of adverse events. [21] Overall, the potency ratio of fentanyl to morphine has a range of 60–100:1. After conducting a series of pilot study, we originally performed this study under the hypothesis that the potency ratio of oxycodone to fentanyl was 60:1.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been demonstrated that oxycodone produced similar or less sedation compared to fentanyl in several recent studies. [18,20,21] In addition, median doses of opioid consumed 30 minutes postsurgery was oxycodone 3.5 mg (range: 2.4–5.4 mg) and fentanyl 64 μg (range: 49–120 μg), this meant to be relatively few oxycodone consumption during this time period.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being most frequently used orally, in recent years, its intravenous use has increased. Its potency is about 1/75 of fentanyl, and in some studies has shown great potency up to 1/60 [48,49].…”
Section: Oxycodonementioning
confidence: 99%
“…Hwang et al [19] reported that the potency ratio was 1:75 in laparoscopic cholecystectomy, and oxycodone showed comparable effects for pain relief compared to fentnayl in spite of a smaller cumulative PCA dose. In other recent studies, the potency ratio of fentanyl and oxycodone was found to be 1:62.5 in gastrointestinal laparotomy, 1:60 in laparoscopic benign gynecological surgery, and 1:55 in colorectal surgery, and oxycodone was shown to provide similar analgesic efficacy to that of fentanyl [20][21][22].…”
mentioning
confidence: 99%
“…Oxycodone is an effective analgesic agent for visceral pain and somatic pain, but studies to date have shown that it is more effective for visceral pain [7][8][9]27]. Likewise, pain after abdominal surgery is controlled by similar or smaller amounts of oxycodone compared with the equipotent ratio of morphine or fentanyl [16][17][18][19][20][21][22]. Therefore, in somatic pain such as pain after orthopedic surgery, the amount of oxycodone should be higher than the dose used for visceral pain.…”
mentioning
confidence: 99%